Training pathway for small bowel capsule endoscopy in the UK. Issue 3 (18th May 2021) - Tai, Foong Way David; Parker, Clare; Sidhu, Reena; McAlindon, Mark; Davison, Carolyn; Smith, Geoff V; Panter, Simon
Abstract : The demand for small bowel (SB) capsule endoscopy (CE) is increasing in the UK. However, there remains a wide variation in the number of CE procedures performed in different centres. Across the UK there is a lack of a clear training pathway or certification process. A standardised national Joint Advisory Group (JAG) on Gastrointestinal Endoscopy approved a 1-year training and accreditation programme accessible to all professional groups that may wish to train in SB CE. Structured training is delivered using JAG-accredited CE courses and an electronic learning module. Prior to setting a knowledge-based assessment, a minimum of 50 SB CE cases are recommended to be read in tandem with a trainer at a local centre, with proficiency documented using Direct Observation of Procedural Skill (DOPS) assessments.